1987
DOI: 10.1177/35.10.3624852
|View full text |Cite
|
Sign up to set email alerts
|

Molecular demarcation of surface domains as established by label-fracture cytochemistry of boar spermatozoa.

Abstract: We used "label-fracture" (J Cell Biol 99:1156, 1984) to establish high-resolution maps of wheat germ agglutinin (WGA) and concanavalin A (ConA) receptor sites on the cell surface of boar spermatozoa and to investigate the possible association of these receptors to integral membrane components. Label-fracture reveals intense WGA labeling over the region of the plasma membrane that overlies the acrosome, including the equatorial segment. The density of WGA receptors decreases from the post-acrosomal area to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…The mean density of PLA2-CG labeling over the E face is relatively low (25.8 k 1.8 particles/m2; see Figure 18). We then used the label-fracture technique to examine the distribution of PLAz-CG labeling over the sperm head, since label-fracture is a high-resolution method for labeling cell surfaces (Kan and Pinto da Silva, 1987). As expected, label-fracture preparation of boar spermatozoa also showed a uniform distribution of PLA2-CG labeling over the E face of the sperm head ( Figure 2), confirming the results obtained by fracture-label shown in Figure 1.…”
Section: Fracture-label Cytochemistrysupporting
confidence: 81%
See 1 more Smart Citation
“…The mean density of PLA2-CG labeling over the E face is relatively low (25.8 k 1.8 particles/m2; see Figure 18). We then used the label-fracture technique to examine the distribution of PLAz-CG labeling over the sperm head, since label-fracture is a high-resolution method for labeling cell surfaces (Kan and Pinto da Silva, 1987). As expected, label-fracture preparation of boar spermatozoa also showed a uniform distribution of PLA2-CG labeling over the E face of the sperm head ( Figure 2), confirming the results obtained by fracture-label shown in Figure 1.…”
Section: Fracture-label Cytochemistrysupporting
confidence: 81%
“…It has been suggested that the regional specificity of sperm membranes is decided mainly by differences in the organization of plasma membrane constituents in individual membrane domains (Tesarik and Flechon, 1986). When mammalian spermatozoa are in different physiological states, the flow of molecules in the regionalization of the membrane is differentially modulated ( Cowan et al, 1987;Kan and Pinto da Silva, 1987;Myles et al, 1987;Wolf, 1987;Wolf et al, 1986;O'Rand. 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Such proteins could then act as a ''fence'' to keep basigin, and presumably other diffusing proteins, corralled within either the principal piece or midpiece membrane domain. This idea is supported by freeze-fracture analysis of the membrane directly over the annulus, which shows circumferential rows of tightly aligned particles (presumably transmembrane proteins) visible on the E-face of the membrane [19,20,[46][47][48]. One transmembrane protein, Tat1, an anion transporter, has also been localized to the membrane directly over the annulus, and it has been suggested that it binds this structure and thus could participate in such a fence [49].…”
Section: Discussionmentioning
confidence: 99%
“…C: Label-fracture permits the high resolution mapping of surface domains of different composition. This example, from the study of Kan and Pinto da Silva (1987), shows the distribution of wheat germ agglutinin receptors in boar sperm. A high labeling density occurs in a margin, free of IMP, a t the base of the head.…”
Section: Prefracture Labeling and "Sectioned Replicas"mentioning
confidence: 94%
“…Label that does not correspond to any structural component visible on the E face is, of course, easily visualized as well. Some of the most impressive demonstrations of the potential of label-fracture for the high-resolution mapping of membrane domains of different composition have been provided by recent studies on the sperm cell (Kan and Pinto da Silva, 1987;Fig 7C). The technique is also capable, at low magnification, of providing extensive survey views of cell surface receptor distribution.…”
Section: Prefracture Labeling and "Sectioned Replicas"mentioning
confidence: 99%